2018
DOI: 10.20892/j.issn.2095-3941.2018.0023
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of factors related to non-sentinel lymph node metastasis in 296 sentinel lymph node-positive Chinese breast cancer patients

Abstract: Objective:Axillary lymph node dissection (ALND) may be unnecessary in 20%–60% of breast cancer patients with sentinel lymph node (NSLN) metastasis. The aim of the present study was to review the medical records of Chinese patients with early-stage breast cancer and positive NSLN metastasis to identify clinicopathological characteristics as risk factors for non-NSLN metastasis.Methods:The medical records of 2008 early-stage breast cancer patients who received intraoperative sentinel lymph node biopsy (SLNB) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
2
6
1
Order By: Relevance
“…In addition, the ALN status remains one of the most important prognostic factors. In our present study, only 266 (37.3%) of the patients with 1–2 SLN metastases in the training cohort were demonstrated to have NSLN metastasis after ALND, which is consistent with the results of previous studies 8 , 20 . Thus, more than 60% of the patients received unnecessary ALND.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the ALN status remains one of the most important prognostic factors. In our present study, only 266 (37.3%) of the patients with 1–2 SLN metastases in the training cohort were demonstrated to have NSLN metastasis after ALND, which is consistent with the results of previous studies 8 , 20 . Thus, more than 60% of the patients received unnecessary ALND.…”
Section: Discussionsupporting
confidence: 93%
“…In patients with zero, one, and at least two SLN metastases, the percentages of positive findings in NSLNs were 3.2%, 24.3%, and 64.6%, respectively. Numerous studies have shown that the tumor burden in metastatic SLNs is associated with NSLN metastasis 16 . Our study found that the proportion of NSLN metastasis increased as the number of SLN metastases increased.…”
Section: Discussionsupporting
confidence: 63%
“…Positive axillary lymph nodes at baseline may be converted to negative nodes when the primary disease is sensitive to NAC. Many studies have reported various factors contributing to residual axillary disease found in ALND after a positive SNB in patients without NAC 15,16 . Only a few clinical studies have explored the influencing factors of NSLN metastasis in those whose nodal status converted from cN+ to cN0 after NAC.…”
Section: Introductionmentioning
confidence: 99%
“…In the immunohistochemical analysis of human breast cancer tissue, S1PR1 expression was closely related to lymphatic metastasis 43 . Previously, a large body of experimental evidence has demonstrated that S1PR1 may trigger lymphocyte egress from lymphoid tissues 44,45 .…”
Section: Discussionmentioning
confidence: 99%